Use And Level Of Satisfaction Of Students Of The Faculty Of Dakwah And Communications With Tiktok As A Digital Media In Obtaining Religious Information - Dian Indah Multazam; Rubino Rubino; Mailin Mailin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to determine use and level of satisfaction of students of the Faculty of Dakwah and Communications (FDK) with Tiktok as a digital media in obtaining religious information. This study uses a descriptive analysis method with a qualitative approach. The data used consists of primary sources (interviews) and secondary sources (literature). The results of the study show that the use of TikTok for KPI FDK students can provide benefits in fulfilling religious information, even though TikTok is not the main source of knowledge. TikTok's content is concise and entertaining, sometimes lacking in depth or accuracy. The TikTok algorithm can also limit perspective with a "bubble filter". It is important for TikTok users to remain critical in assessing information and verifying it through reliable sources..